Geopolitics of renewable energy under scrutiny - BENSLIMANE, Ismail; ELOTMANI, Yassire (Revue Internationale des Sciences de Gestion, 2026)
Nowadays, the world is witnessing a shift from a traditional paradigm that encourages the use of non-renewable energy sources to a new one that supports the development and adoption of renewable energy technologies. Given this, several issues arise that require in-depth study regarding the future ramifications of this transition and the challenges faced by stakeholders. To this end, the current work aims to examine the ultimate goals of the energy transition, the potential reordering of countries and the establishment of a new global order, the repercussions of this transition on international relations, and the accessibility of renewable energy for all countries without discrimination or restriction. Furthermore, it investigates the challenges of the energy transition in terms of the availability of critical materials and cybersecurity risks.